Dobra doczesne a nadzieja życia wiecznego z perspektywy Ojców Kościoła - Żurek, Antoni (Vox Patrum, 2013)
The question about the sense of life was not formulated by Church Fathers directly. Despite that, their texts indicate the elements which give value for human life and are the protection against death. Material world and social structures can’t satisfy man because inside his heart there is an unquenchable desire. In fact, according to the Church Fathers, man longs for the life with God in eternity. That desire is satisfied by hope which is based on the Christian faith. That’s the Christian hope of eternal life that makes the temporal life bearable and valuable. This is not only the Revelation teaching but also the result of rational calculation. Man not always adequately recognizes the essence of his desires and therefore it is the Church and its shepherds task to correctly allocate the hope because hope should later organize the whole human life.